Strategi Pengemasan Pesan Fotografi dalam Visual Branding oleh CV Hagamo Mahakarya Indonesia - Fauzi, Ilham Herda; Sukanda, Ukon Furkon; Khairani, Aulian (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Currently, the development of the fashion industry is very rapid, as evidenced by the many varied products. Many people prefer global brands over local brands. However, this is no longer the case because currently local brands are able to compete with other global brands. One local brand that has good quality is CV Hagamo Mahakarya Indonesia, which is located in Tangerang Regency. The aim of this research is to find out how photography packaging strategies can improve visual branding by CV Hagamo Indonesian Masterpiece. This research uses qualitative methods with the aesthetic theory of visual communication. Data collection techniques were carried out using interviews, observation and documentation. The research results show that CV Hagamo Mahakarya Indonesia applies the concept of visual communication in the form of videos, photos and attractive designs to support its sales in the marketplace. With this strategy, Hagamo can build a positive image in the eyes of consumers, expand the reach of brand recognition, and increase interest and interest in Hagamo Official products.